Parent Vessel Size and Curvature Strongly Influence Risk of Incomplete Stent Apposition in Enterprise Intracranial Aneurysm Stent Coiling - Heller, R.S.; Malek, A.M. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Flexible microstents, such as the closed-cell EN, have facilitated adjunctive coiling of intracranial aneurysms. Little data are available on the ability of the stent struts to maintain vessel-wall apposition once deployed in the tortuous cerebral vasculature and the prevalence of ISA. The purpose of this study was to evaluate the relationship between geometric features of the parent vessel at the stent deployment site and prevalence of ISA. MATERIALS AND METHODS: Postprocedural 3T-MRA was performed in a cohort of 39 patients undergoing EN stent-assisted intracranial aneurysm coiling. 3T-MRA was analyzed for the presence of ISA and supplemented by angiographic C-arm FPCT (DynaCT). Parent vessel diameter, curvature radius, and stent-subtended arc angle were measured at the site of deployment and analyzed for prediction of ISA in the ICA. RESULTS: 3T-MRA uncovered a unique crescent flow pattern (CS) outside the EN struts, which was confirmed by FPCT to indicate ISA resulting from EN crimping. ISA was detected on 3T-MRA in 19/39 patients (49%). Univariate analysis revealed ISA in the ICA to correlate with a large stent-subtended angle, a small curvature radius, and a large diameter but not stent length or jailing versus a sequential technique. Multivariate analysis identified ISA to correlate with vessel-curvature radius (OR, 253; P = .009), stent-subtended angle (OR, 225; P = .005), and parent vessel diameter (OR, 8.49; P = .044). CONCLUSIONS: In this study, ISA was detectable by 3T-MRA in a significant proportion of patients undergoing EN stent-assisted coiling of ICA aneurysms in a vessel geometry− and stent-deployment location−dependent manner. This characteristic of EN coiling at this potentially tortuous location should be taken into account when selecting an endovascular strategy. CScrescent signCS+CS presentCS−CS absent3D-RA3D rotational angiographyDSAdigital subtraction angiographyENEnterprise stent or vascular reconstruction deviceFPCTflat panel CTICAinternal carotid arteryISAincomplete stent appositionMPRmultiplanar reformationORodds ratio3T-MRA3T time-of-flight MR angiography